An exploratory analysis of changes in mood, anxiety and craving from pre- to post-single sessions of exercise, over 12 weeks, among patients with alcohol dependence. (October 2016) - Brown, Richard A.; Prince, Mark A.; Minami, Haruka; Abrantes, Ana M.
Abstract: Aerobic exercise is currently being studied as a relapse prevention strategy for individuals with alcohol use disorders. Negative affect and cravings predict relapse. The acute effects of moderate-intensity exercise have been shown to improve mood and reduce craving. The current study examined the acute effects of exercise on changes in mood, anxiety, and craving from pre- to post-exercise at each week of a 12-week moderate intensity exercise intervention with sedentary alcohol dependent adults. Twenty-six participants in the exercise condition of a larger randomized clinical trial (Brown et al., 2014) exercised in small groups at moderate intensity for 20–40 min per session. Participants rated mood, anxiety, and cravings in the present moment before and after each exercise session over the course of the 12-week intervention. Data analyses focused on effect size and interval estimation. Joinpoint analysis was used to model longitudinal trends. Increases in mood and decreases in anxiety and craving were apparent at every session. Effect size estimates revealed that average change from pre- to post-exercise was in the small to medium range with some individual sessions reaching the large range. Joinpoint analyses revealed that the pre-post exercise changes in mood increased, anxiety remained stable, and craving diminished across the 12 weeks. This study provides provisional support for a change in mood, anxiety and alcohol cravings for the role of exercise in the early recovery period for alcohol dependence. Acute single bouts of moderate-intensity exercise may help individuals with alcohol dependence manage mood, anxiety, and craving thereby reducing relapse risk, but further research is needed with a more rigorous study design. Highlights: Acute effects of exercise have been shown to improve mood and reduce craving. Acute effects of exercise were examined in alcohol dependent adults over 12 weeks. Effect size estimates pre to post exercise were mostly in the small to medium range. Single bouts of exercise may help alcohol dependent persons manage mood and craving.